2004
DOI: 10.1002/eji.200425369
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of modulation of T cell responses by N‐palmitoylated peptides

Abstract: Small structural changes in the antigenic peptides recognized by TCR can alter the biological properties of those peptides and convert them into weak agonists, partial agonists, or antagonists of these receptors. These altered peptide ligands (APL) are usually generated by conservative amino acid substitutions at TCR contact residues. Here, we show that APL with therapeutic properties can also be generated by attachment of palmitic acid at the N terminus of the peptide without the need to modify the peptide's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Furthermore, they showed that an N-palm PLP peptide was able to actively suppress the response to the nonacylated peptide (32). Bueno et al (33) found that an N-palm peptide of pigeon cytochrome C could interact with a MHC class II-restricted CD4 ϩ T cell clone, but this interaction was not nearly as robust as that occurring with the nonpalmitoylated peptide; indeed N-palmitoylation of the peptide converted it into a weak agonist that could then only induce T cell anergy. A possible explanation for all of these observations with N-palm peptides is that the peptides are forming multimers, as we have found in our system, thus inhibiting formation of the trimolecular complex of MHC/peptide/TCR to some degree.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they showed that an N-palm PLP peptide was able to actively suppress the response to the nonacylated peptide (32). Bueno et al (33) found that an N-palm peptide of pigeon cytochrome C could interact with a MHC class II-restricted CD4 ϩ T cell clone, but this interaction was not nearly as robust as that occurring with the nonpalmitoylated peptide; indeed N-palmitoylation of the peptide converted it into a weak agonist that could then only induce T cell anergy. A possible explanation for all of these observations with N-palm peptides is that the peptides are forming multimers, as we have found in our system, thus inhibiting formation of the trimolecular complex of MHC/peptide/TCR to some degree.…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesized that the palmitoyl group directly participated in stabilizing the peptide displayed on the MHC-TCR complex during antigen presentation (84). These findings had implications for modulating the immunogenicity of synthetic peptides attached to palmitic acid (85). …”
Section: Palmitic Acidmentioning
confidence: 99%
“…Moreover, results from vaccine research has shown that acylation with fatty acids can boost the immune response [ 7 , 8 ]. On the other hand, a decrease in the stimulatory capacity for a peptide linked to palmitic acid has also been observed in vivo [ 9 ] as well as in vitro [ 10 ].…”
Section: Introductionmentioning
confidence: 99%